Impact of Preoperative and Postoperative Antibiotic Use on Surgical Site Infection Rates in General Surgery Patients - A Clinical Study - SHAH, MUHAMMAD TAIMOOR; KAUSAR, SALMA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Despite significant advances in surgical practice, Surgical Site Infections (SSIs) continue to be one of the most common postoperative complications and remain the leading cause of patient morbidity, prolonged hospital stay, and increased healthcare costs. Preoperative and postoperative use of antibiotics is a key strategy to reduce the incidence of SSIs, especially in surgeries. Aim: To evaluate the effect of preoperative and postoperative antibiotic usage on the risk of surgical site infections in general surgical patients in two tertiary care hospitals of Lahore, Pakistan. Methodology: A prospective clinical study was carried out from October 2024 to December in Jinnah Hospital and Lahore General Hospital Lahore Pakistan. Non probability consecutive sampling was used to enroll a total of 100 patients who were scheduled or undergoing elective or emergency general surgical procedures. Two groups (A, n=50, received preoperative prophylactic antibiotics; B, n=50, received both preoperative and postoperative antibiotics) were formed according to antibiotic timing. Incidence of SSIs within 30 days post-surgery, clinically and/or microbiologically, was the primary outcome. Demographic, comorbidities, type of surgery and duration of hospital stay data were also collected. Results: Out of 100 patients, 18 developed SSIs. The infection rate for Group A was 14% (7 of 50) and for Group B, it was 11% (6 of 50). Nevertheless, this difference was not statistically significant (p > 0.05). Notably, the SSI prevalence was higher in patients with diabetes and in those undergoing emergency surgery, regardless of antibiotic strategy. In addition, 5 patients had SSIs despite extended postoperative antibiotic coverage, implying limited added benefit and possibly antibiotic overuse. Conclusion: Preoperative prophylactic antibiotics did not reduce surgical site infection rates, compared to given postoperatively. More emphasis should be placed on appropriate timing and antibiotic stewardship than on extended antibiotic use.